The Outbreak of Human Monkeypox in 2022: A Changing Epidemiology or an Impending Aftereffect of Smallpox Eradication? - Al-Tammemi, Ala’a B.; Albakri, Rana; Alabsi, Suhib (Frontiers in Tropical Diseases, 2022)
This article presents a concise mini review about human monkeypox (MPX), in response to the current outbreak in non-endemic countries. MPX is one of the viral zoonotic diseases which is attributed to monkeypox virus (MPXV) and causes a smallpox-like disease. Despite its ability to infect various mammals, the animal reservoir for MPXV is still unconfirmed. The disease usually lasts for an average of 2-4 weeks before complete recovery. The incubation period for MPXV ranges from 5-21 days and the illness starts with prodromal phase, which is characterized by fever, chills, muscle pain, back pain, general malaise, lymph node enlargement, and headache, followed by rash. MPX is a self-limited illness with spontaneous recovery in most cases. In the middle of May 2022, an outbreak of human MPX has been declared by the World Health Organization (WHO) across various WHO regions, and in countries that are not endemic for the disease. As of June 08, 2022, the number of confirmed MPX cases that were reported across 18 countries of European Union/European Economic Area (EU/EEA) has reached 704 cases. Worldwide, and as of June 08, 2022, a total of 1285 confirmed MPX cases were reported in non-endemic countries across four WHO regions. Exportation of MPXV from Africa to other continents has been increasingly reported. Lacking travel connections to Africa among most current reported cases in 2022 raises an alarm about the changing epidemiology of the disease which warrants a stringent epidemiological surveillance to prevent further escalation of the current outbreak in non-endemic countries.